2016
DOI: 10.2495/uw160231
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of land cover change on stream discharges in Luvuvhu River Catchment, Vhembe District, Limpopo Province, South Africa

Abstract: Luvuvhu River Catchment experiences floods resulting from heavy rainfall intensities exceeding 15 mm per hour. The generation of runoff is triggered by the rainfall intensity and soil moisture status. In this study, remote sensing and GIS techniques were used to analyse the hydrologic response to land cover changes. Runoff was calculated as a product of the net precipitation and a curve number coefficient. It was then routed using the Muskingum-Cunge method using a diffusive wave transfer model that enabled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The area’s relief consists of undulating terrain with plains, hills and mountains that cover an area of approximately 67,000 hectares (ha). The climate is primarily influenced by the intertropical convergence zone [ 27 ]. Rainfall distribution in the area is classified as unimodal, with a rainy season predominantly between October and January [ 28 ].…”
Section: Study Areamentioning
confidence: 99%
“…The area’s relief consists of undulating terrain with plains, hills and mountains that cover an area of approximately 67,000 hectares (ha). The climate is primarily influenced by the intertropical convergence zone [ 27 ]. Rainfall distribution in the area is classified as unimodal, with a rainy season predominantly between October and January [ 28 ].…”
Section: Study Areamentioning
confidence: 99%
“…Excessive rainfall is regarded as the main parameter that causes floods and understanding the frequency and climatology of such extreme rainfall events is key in developing measures towards improving coping strategies in any region (Musyoki et al, 2016). Therefore, improving the knowledge of weather systems (tropical lows and cut-off lows) that influence rainfall patterns could help farmers to cope with the effects of extreme rainfall events (Singo et al, 2016). Previous research has revealed that farmers rely on different sources of weather information, such as agricultural extension officers, television or radio, newspapers, friends and cellphones, but poor understanding of the weather information and inaccurate weather forecasts decrease the reliability of forecasts, resulting in farmers being exposed to flood impacts (Armah et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of drought and floods is common in the Luvuvhu River catchment (LRC), impacting negatively on crop production and agricultural income as a result of reduced crop sales, harvest failure and livestock mortality (Devereux, 2007;Mathivha et al, 2016). Rainfall variability can result in either drought or floods and affects agricultural production in especially rain-fed farming areas (Afifi et al, 2016;Kori et al, 2012;Murali and Afifi, 2014;Oseni and Masarirambi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The total area under study is approximately 67,000 ha, with an even distribution of hills, plains, and mountains. The area is characterised by unimodal rainfall distributions, where the rainy season is between October and January, with an average annual rainfall of between 200 and 400 mm [42][43][44]. The total area under study is approximately 67,000 ha, with an even distribution of hills, plains, and mountains.…”
Section: Methodsmentioning
confidence: 99%